A new hope: introducing comprehensive sex education to a Christian secondary school in Uganda after repeal of parliamentary ban - Jaclyn A Boozalis; Margaret H Nakibuule; Janet P Realini; Jason Rosenfeld (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background One quarter of Ugandan girls aged 15-19 years have become pregnant, and by age 50, one quarter of women report experiencing a sexually transmitted infection (STI). Adolescent pregnancies pose health challenges because teenage mothers are constrained in their future pursuit of education and have an increased likelihood of adverse pregnancy outcomes. Uganda lifted a parliamentary ban on sexual education beyond abstinence in May 2018. This study aimed to introduce and evaluate a comprehensive sex education curriculum to prevent pregnancies and sexually transmitted infections at a secondary school in Uganda. # Methods Over three weeks in June 2018, our team implemented a comprehensive reproductive health education curriculum called 'big decisions' in a secondary school in Uganda. Hope Comprehensive High School is a Christian school in Masaka, Uganda with approximately 400 students. We trained 15 teachers and co-facilitated the curriculum with a pilot group of 30 students. We measured student demographics and knowledge/attitudes toward sex, relationships, STIs, and contraception before and after the program. # Results There was a statistically significant improvement in student knowledge about pregnancy, contraceptives, and STIs. We also noted an increase in positive attitudes toward condom use. # Conclusions Engaging the faculty and staff with an appropriate and fact-based curriculum was crucial to the success of the project. Myths on contraceptive education and condoms were significantly debunked within the pilot group. This project demonstrates the viability of a non-faith based sex education curriculum in a Christian Ugandan secondary school.